Real Estate Tax, Housing Price, and Housing Wealth Effect: An Empirical Research on China Housing Market - Jixuan Zhang; Xiaoyu Deng (Discrete Dynamics in Nature and Society, 2022)
Housing market occupies a large part of the wealth of the whole society in most countries, and real estate tax plays an important role for the government to maintain sustainable development for the economy. As consumption being a major issue nowadays, in this paper, we want to find out (1) whether real estate taxes affect the house price in China and whether the affects vary among different tax types? (2) whether there exists wealth effect in China housing market? That is, whether the change in house wealth (price) affects the consumption? (3) whether and how do real estate taxes affect wealth effect? We set up the empirical model by using the GMM method on panel data from 2002 to 2016 to explore the relations among real estate tax, housing price, and wealth effect. We considered the influence of four different types of real estate tax on the housing price and found the results are mixed. Besides, there is a significantly negative wealth effect on China housing market. Finally, house price plays a mediator role in the effect of the real estate tax on the consumption.